Decreased bone mineral density in ovariectomized mice is ameliorated after subsequent repeated intermittent administration of (R)‐ketamine, but not (S)‐ketamine - Yuko Fujita; Kenji Hashimoto (Wiley, 2020)
Abstract Aim Depression is a common symptom in people with osteoporosis. (R)‐ketamine produced greater potency and longer‐lasting antidepressant‐like actions than (S)‐ketamine in rodents. Here, we examined the effects of two ketamine enantiomers on the reduced bone mineral density (BMD) in the ovariectomized (OVX) mice which is an animal model of postmenopausal osteoporosis. Methods Female ddY mice were OVX or sham‐operated. Subsequently, saline (10 mL/kg/d, twice weekly), (R)‐ketamine (10 mg/kg/d, twice weekly), or (S)‐ketamine (10 mg/kg/d, twice weekly) was administered intraperitoneally into OVX or sham mice for the 6 weeks. The femur from all mice was collected 3 days after the final injection, and BMD in the femur was measured. Results The reduction of cortical BMD and total BMD in the OVX mice was significantly ameliorated after subsequent repeated intermittent administration of (R)‐ketamine, but not (S)‐ketamine. Conclusion The study shows that (R)‐ketamine can ameliorate the reduced cortical BMD and total BMD in OVX mice. Therefore, (R)‐ketamine would be a novel therapeutic drug for women with osteoporosis.